Ad Palatinas acipensem mittite mensas: Fish remains from Viminacium - Živaljević Ivana R.S.; Vuković-Bogdanović Sonja I.; Bogdanović Ivan S. (Starinar, 2019)
The paper presents the results of archaezoological analysis of fish remains from three locations at Viminacium (the Amphitheatre, Nad Klepečkom and Pirivoj), discussed jointly with finds of fishing equipment and relevant written sources on the subject. Albeit small and biased due to the hand-collection of animal bones, the fish faunal assemblage from Vimincium provides valuable data on the choice of exploited species, fishing and fish transportation practices, and patterns of consumption and deposition in the city and its surroundings. In addition to remains of locally available freshwater fish, occurring at all three sites, the Amphitheatre sample contained the remains of large anadromous sturgeons, possibly obtained from the downstream, Iron Gates area. Their size, contextual provenance, as well as their exceptional status according to written sources, indicates that there had been notable differences in access to high-quality fish among the different social classes at Viminacium. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. III 47018: Viminacium, Roman city and military camp - research of the material and non material culture of inhabitants by using the modern technologies of remote detection, geophysics, GIS, digitalization and 3D visualization and Grant no. III 47001: Bioarchaeology of Ancient Europe - humans, animals and plants in the prehistory of Serbia]